Artemisia argyi water extract promotes selenium uptake of peach seedlings - Lin, Lijin; Wang, Jiangyue; Liao, Ming’an; Hu, Rongping; Deng, Qunxian; Wang, Zhihui; Wang, Xun; Tang, Yi (Frontiers in Plant Science, 2022)
Soil in most areas of the world is selenium (Se) deficient, which results a low Se content in agricultural products. To improve the fruit tree Se accumulation, the effects of different Artemisia argyi water extract concentrations (0, 100, 200, 300, and 400-fold dilutions) on the growth and Se accumulation of peach seedlings were studied by a pot experiment. A 300- and 400-fold dilution of A. argyi water extract increased the root and shoot biomass (dry weight), leaf chlorophyll a content, superoxide dismutase (SOD) activity, and peroxidase (POD) activity of peach seedlings, but decreased the leaf chlorophyll a/b. Different A. argyi water extract concentrations had no significant effects on peach leaf chlorophyll a content of peach seedlings, but increased the leaf carotenoid content, catalase (CAT) activity, and soluble protein content. Different A. argyi water extract concentrations increased the total Se, inorganic Se, and organic contents in roots and shoots of peach seedlings to some extent. Furthermore, A. argyi water extract concentration exhibited a linear relationship with the root and shoot total Se contents. Compared with the control, the 100-, 200-, 300-, and 400-fold dilutions of A. argyi water extract increased the shoot total Se content by 18.95%, 31.31%, 39.32%, and 51.59%, respectively. Different A. argyi water extract concentrations also increased the leaf Se metabolism-related enzyme activities of peach seedlings, including the activities of adenosine triphosphate sulfurase (ATPS), adenosine 5'-phosphosulfate reductase (APR), and serine acetyltransferase (SAT), as well as selenocysteine methyltransferase (SMT) to some extent. Moreover, correlation and grey relational analyses revealed the root total Se content, CAT activity, and ATPS activity to be closely associated with the total shoot Se content. Therefore, applying A. argyi water extract can thus promote the growth and Se uptake of peach seedlings, and the future study should focus on the application effects of Se uptake in peach fruits.